1832-1842: a Crucial but Forgotten Decade in the Life of Manuel García Jr. (Muse, 2025)
Manuel García Jr. is probably the most renowned among the singing teachers of the 19th century. Such fame, however, is not matched by an in-depth knowledge of his life history, especially regarding the crucial ten-year period between 1832-1842, which starts with the death of his father in 1832 and ends with his achievement as a fully established teacher at the Paris Conservatory in 1842. During this decade, he published two works that had a revolutionary impact on the history of singing: Mémoire sur la voix humaine and Traité Complet de l'Art du Chant. García conceived these works to assert his primacy in the knowledge and teaching of the so-called 'voix sombrée', the vocal emission that was considered highly topical in Paris after Duprez's return from Italy. The link between García, Duprez, the operatic repertoire of the 1830s and the 'voix sombrée' can be found in the life and work of Manuel and his first famous pupil and first wife, Eugénie, in Italy from 1835 to 1839. In Italy, they became acquainted with the works of Bellini and Donizetti in the early days of their dissemination. The literature on García has long ignored many of the key events of this crucial period and has often assigned incorrect dates to both the publication of his teaching works and the start of his professorship at the conservatory. This study aims to fill this significant gap, in order to fully highlight the role played by García during the period that saw the transition of vocal art from bel canto to melodrama.
Keywords: Manuel García Jr.; Traité Complet de l’Art du Chant; Mémoire sur la Voix Humaine; Voix sombrée; Eugénie García Mayer